Experiencing the Loss of an Adult Child in Old Age - A.A. Agisheva (Клиническая и специальная психология)
Parental grief is associated with many collateral losses and severe consequences at the mental, physical, and social levels. Most studies of parental loss are concentrated in the area of infant mortality, while increasing life expectancy entails an increase in the number of cases of adult child loss among older people. Anamneses of elderly people are often burdened by cumulative psychotraumatization, somatic and mental disorders. At the same time, older subjects have a wider range of coping strategies available. This review examines the consequences of the superposition of the factors of the severity of the stressor under study and the pronounced gerontogenetic diversity. Based on the analysis of 76 literary sources, a comparison and specification of the empirical research results were carried out, which preliminary revealed universal psychological consequences of losing a child at an older age, including a sense of guilt, a feeling of abnormality of what happened, complication of the age crisis, deformation of the "Self-concept", chronification of grief. Specific tendencies in the course of grief due to the type of loss are systematically described. Loss of a violent nature is the most traumatic in comparison with loss due to an unfavorable outcome of the disease and is accompanied by the desire of parents to take revenge, restore justice. Losses of children performing official duties during military operations are associated with extremely high ambivalence of experiences, while losses associated with emergency situations are associated with survivor's guilt. Illegal grief (death due to a stigmatized disease, suicide, violation of the law, substance use) is burdened by shame, which prevents getting help. The study points out the need for empirical clarification of the data obtained and has practical value, specifying the targets of providing psychotherapeutic assistance to grieving elderly parents.